Sammy, the Seal - Hoff, Syd (New York, 1980)
Upon discovering what it is like outside the zoo, Sammy decides there is no place like home.
Accelerated Reader AR
Reading Counts!
Keywords: Children; Seal; Animals; Early chapter book